An exploratory analysis to identify behavior change techniques of implementation interventions associated with the implementation of healthy canteen policies. Issue 8 (5th May 2021) - Yoong, Sze Lin; Hall, Alix; Stacey, Fiona; Nathan, Nicole; Reilly, Kathryn; Delaney, Tessa; Sutherland, Rachel; Hodder, Rebecca; Straus, Sharon; Wolfenden, Luke
Abstract: Empirical studies to disentangle the effects of multicomponent implementation interventions are needed to inform the development of future interventions. This study aims to examine which behavior change techniques (BCTs) primarily targeting canteen manager are associated with school's healthy canteen policy implementation. This is a secondary data analysis from three randomized controlled trials assessing the impact of a "high, " "medium, " and "low" intensity intervention primarily targeting canteen managers on school's implementation of a healthy canteen policy. The policy required primary schools to remove all "red" (less healthy items) or "banned" (sugar sweetened beverages) items from regular sale and ensure that "green" (healthier items) dominated the menu (>50%). The delivery of BCTs were retrospectively coded. We undertook an elastic net regularized logistic regression with all BCTs in a single model. Five k -fold cross-validation elastic net models were conducted. The percentage of times each strategy remained across 1, 000 replications was calculated. For no "red" or "banned" items ( n = 162), the strongest BCTs were: problem solving, goal setting (behavior), and review behavior goals. These BCTs were identified in 100% of replications as a strong predictor in the cross-validation elastic net models. For the outcome relating to >50% "green" items, the BCTs problem solving, instruction on how to perform behavior and demonstration of behavior were the strongest predictors. Two strategies were identified in 100% of replications as a strong (i.e., problem solving) or weak predictor (i.e., feedback on behavior). This study identified unique BCTs associated with the implementation of a healthy canteen policy.